Desinvestimento direto estrangeiro das empresas multinacionais de saneamento na América do Sul - Nunes, Neusa Santos de Souza (2018)
This paper aims to propose a conceptual model of the institutional factors that influence the foreign direct divestment of companies in the basic sanitation sector (water supply, collection and sewage treatment) in Latin America, particularly in Argentina, Brazil, Bolivia, Colombia and Uruguay. This issue is relevant because South America was one of the regions most affected by the cancellation of public-private partnership agreements in infrastructure over the last 30 years. The focus was the public-private partnership (PPP) contracts, with participation of the foreign private sector, in which the international private partner somehow canceled its participation in the period between 1990 and 2010. To reach the objective proposed, we chose the multiple case study method structured through documentary analysis and interviews. The cases studied were relevant, since several South American countries engaged in strategies to modernize their economies receiving substantial direct foreign investment, but there was a massive exit from these investors. In particular, this paper proposes that the exit of three companies (Agbar, Veolia and Suez) from their operations in South American countries (Argentina, Brazil, Bolivia, Colombia and Uruguay) is related to common factors that include ex post regulation of the concession and contractual renegotiation.